Reactive Astrocytes Are Key Players in Nigrostriatal Dopaminergic Neurorepair in the Mptp Mouse Model of Parkinson’s Disease: Focus on Endogenous Neurorestoration - L.’Episcopo, Francesca; Tirolo, Cataldo; Testa, Nuccio; Caniglia, Salvo; Concetta Morale, Maria; Marchetti, Bianca (Current Aging Science, 2013)
Parkinsons’disease (PD), a common neurodegenerative disorder, is characterized by progressive loss of dopaminergic (DAergic) neurons in the subtantia nigra pars compacta (SNpc) and gliosis. The cause and mechanisms underlying the demise of nigrostriatal DAergic neurons are not completely clarified, but interactions between genes and environmental factors are recognized to play a critical role in modulating the vulnerability to PD. Current evidence points to reactive glia as a pivotal factor in PD, but whether astroglia activation may protect or exacerbate DAergic neuron loss is presently the subject of much debate. Astrocytes and microglia are the key players in neuroinflammatory responses, by secreting an array of pro- and anti-inflammatory cytokines, anti-oxidant and neurotrophic factors. Here, the contribution of astrocytes and their ability to influence DAergic neurodegeneration, neuroprotection and neurorepair will be discussed. In particular, the dynamic interplay between astrocyte-derived factors and neurogenic signals in MPTP-induced plasticity of nigrostriatal DAergic neurons will be summarized together with recent findings showing that reactive astrocytes may contribute to promote DAergic neurogenesis from midbrain adult neural stem/precursor cells (NPCs). Within a host of astrocyte- derived factors, we unveiled Wingless-type MMTV integration site (Wnt)/β-catenin signalling was unveiled, as a strong candidate in MPTP-induced DAergic neuroplasticty/neurorepair. Understanding the intrinsic plasticity of nigrostriatal DAergic neurons and decifering the signals facilitating the crosstalk between astrocytes and midbrain neuroprogenitors may have implications for the role of stem cells technology in PD and for identifying potential therapeutic targets to promote endogenous neurorepair.
Keywords: neuroprotection